Looking deeper : multimodal and contrast-enhanced photoacoustic imaging offer a clearer view within tissues for more accurate diagnosis - Pramanik, Manojit (2015)
Optical imaging modalities such as fluorescence (FL) microscopy, multiphoton microscopy, and optical coherence tomography (OCT) have been well established for high optical contrast and high spatial resolution imaging of biological tissues. However, as they are dependent on ballistic photons, these methods fail to image beyond ~1 mm or so inside biological tissue. In contrast, diffuse optical imaging (DOI), which uses multiple scattered photons for imaging, can image much deeper (up to a several centimeters) into the tissue. Unfortunately, due to strong light scattering in tissues, it fails to maintain the high resolution at the deeper imaging depth. Photoacoustic imaging (PAI) bridges this gap of imaging deeper with high resolution and contrast by combining optical excitation with acoustic detection [1].